Optimization of Lipase-Catalyzed Transesterification of Cotton Seed Oil for Biodiesel Production Using Response Surface Methodology - Li,Ying Xia (2016)
The aim of this work was to study the biodiesel production from cotton seed oil by lipase produced by Pichia guilliermondii lipase, which was immobilized onto hydrophobic magnetic particles (HMPs). The optimum reaction conditions were determined for lipase dosage, methanol-to-oil molar ratio, temperature and water content. Using response surface methodology, a quadratic polynomial equation was obtained for fatty acid methyl esters (FAMEs) content by multiple regression analysis. Verification experiments confirmed the validity of the predicted model. The optimal conditions for the enzymatic transesterification were temperature of 38.76℃, 31.3% immobilized lipase, 10.4% water content, and a methanol-to-oil molar ratio of 4.715:1. The gas chromatography- mass spectrometry showed that biodiesel was mainly composed of the methyl esters of hexadecanoic, 9,12-octadecadienoic and 9-octadecadienoic acid.